2010
DOI: 10.1002/fuce.200900016
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Impurity Concentration Effects on Degradation of Nickel/Yttria‐stabilised Zirconia Anode in PH3‐Containing Coal Syngas

Abstract: Degradation of the Ni/yttria‐stabilised zirconia (YSZ) anode of the solid oxide fuel cell has been evaluated in the coal syngas containing different PH3 concentrations in the temperature range from 750 to 900 °C. Thermodynamic equilibrium calculations show that PH3 in the coal syngas gas is converted mostly to P2O3 at 750–900 °C. The phosphorous impurity reacts with the Ni‐YSZ anode to form phosphates. The P‐impurity poisoning leads to the deactivation of the Ni catalyst and to the reduction in the electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…But the precipitate phase cannot be identified in this study. In the Ni/YSZ anode SOFCs, the PH 3 can react with Ni in the all cells in previous works [19,20,[104][105][106][107]. In this study, similar morphology changes were observed.…”
Section: Effect Of Ph 3 On Ni In Anode Of Sofcssupporting
confidence: 84%
See 2 more Smart Citations
“…But the precipitate phase cannot be identified in this study. In the Ni/YSZ anode SOFCs, the PH 3 can react with Ni in the all cells in previous works [19,20,[104][105][106][107]. In this study, similar morphology changes were observed.…”
Section: Effect Of Ph 3 On Ni In Anode Of Sofcssupporting
confidence: 84%
“…So it is essential to examine the effect of the contaminant on the SOFCs performance in terms of structure and chemistry changes. PH 3 is an interesting contaminant, which was investigated by different research groups in Ni/YSZ anode SOFCs [19,20,[104][105][106][107] or other anode SOFCs [108,109]. In the Ni/YSZ anode SOFCs, the PH 3 can react with Ni in the all cells in those previous works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As little as 0.5 ppmv of phosphorous species in syngas can result in a degradation of SOFC power density . Phosphorous‐containing species segregates at grain boundaries in the anode as nickel phosphide/phosphate and zirconia phosphate, which reduces the electronic conductivity of the anode and inhibits the YSZ network for oxygen ion transport . High steam levels are thought to resist anode poisoning by phosphorous …”
Section: Emissions and Abatementmentioning
confidence: 99%
“…PH 3 and P x O y have been chosen for P related effects study [30][31][32][33][34][35][36][37][38][39][40][41]. It is been believed that PH 3 might be the main specie in coal syngas, though some gas phase equilibrium calculations showed PH 3 would be oxidized in P x O y form because of the high steam concentration [32].…”
Section: Phosphorus (P)mentioning
confidence: 99%